Differences in nicotine intake and effects from electronic and combustible cigarettes among dual users. (6th January 2020) - St.Helen, Gideon; Nardone, Natalie; Addo, Newton; Dempsey, Delia; Havel, Christopher; Jacob, Peyton; Benowitz, Neal L.
Abstract: Aim: To describe systemic nicotine exposure and subjective effects of electronic cigarettes (e‐cigarettes) in people who use both e‐cigarettes and cigarettes (dual users), including within‐subject comparisons of e‐cigarette and cigarette use. Design: Two‐arm, counterbalanced cross‐over study. Participants used their usual brand of e‐cigarette or cigarette during a standardized session in a 2‐week study. Setting: Hospital research ward, San Francisco, CA, USA. Participants: Thirty‐six healthy (eight women, 28 men) participants. Measurements: Plasma nicotine was analyzed by gas chromatography–tandem mass spectrometry; nicotine withdrawal, urge to smoke and vape, affective states, craving, satisfaction and psychological reward were measured by standardized questionnaires. Findings: Compared with cigarettes, average maximum plasma nicotine concentration (Cmax ) was lower with e‐cigarettes [6.1 ± 5.5 ng/ml, mean ± standard deviation (SD) versus 20.2 ± 11.1 ng/ml, P < 0.001] and time of maximal concentration (Tmax ) was longer (6.5 ± 5.4 versus 2.7 ± 2.4 minutes, P < 0.001). Use of both products resulted in a reduction in the severity of withdrawal symptoms, negative affect and urge to use either product. E‐cigarettes were less rewarding and satisfying and reduced craving to a lesser degree than cigarettes. We were not able to detect any differences in withdrawal symptoms, affective states and urge to smoke cigarettes between e‐cigarette and cigarette use. Conclusion: Systemic nicotine exposure was, on average, lower with single use of e‐cigarettes compared with cigarettes, and e‐cigarettes were judged to be less satisfying and rewarding and reduced craving less than cigarettes.